Superman & Lois. The complete second season [videorecording (DVD)]. - Berlanti, Greg; Helbing, Todd (Warner Bros. Entertainment, 2022)
Season two of Superman and Lois opens with the dust still settling in Smallville following the shocking outcome of last season's confrontation between Morgan Edge and Superman. With Smallville on the national map for the first time in the town's history, Lois Lane faces fresh challenges in her latest journalistic endeavors, while Jordan and Jonathan also find themselves dealing with change.